1979
DOI: 10.1039/c39790000591
|View full text |Cite
|
Sign up to set email alerts
|

Chiral acyl anion equivalents: asymmetric synthesis of α-methoxytolualdehyde

Abstract: Condensation of a chiral dithioacetal mono-Soxide anion with benzaldehyde leads to or-methoxytolu-aldehyde with high chemical and optical yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…1) 7 for these two electrophiles (PhCHO and Ph 2 CO) a precoordination of the carbonyl O atom at the lithium center can be assumed. Second, in accordance with other reactions of lithiated sulfoxides 24,[48][49][50] and also with aldol reactions 51,52 the formation of six-membered cyclic transition states as given in Scheme 3 can be assumed. Based on the experimental findings, the diastereoselectivities observed in this work can be explained in the following way: the formation of the S S R C -and R S S C -configured products 3a and 4b suggests that the two reactions proceed via the transition state ts2.…”
Section: About the Diastereoselectivitymentioning
confidence: 77%
“…1) 7 for these two electrophiles (PhCHO and Ph 2 CO) a precoordination of the carbonyl O atom at the lithium center can be assumed. Second, in accordance with other reactions of lithiated sulfoxides 24,[48][49][50] and also with aldol reactions 51,52 the formation of six-membered cyclic transition states as given in Scheme 3 can be assumed. Based on the experimental findings, the diastereoselectivities observed in this work can be explained in the following way: the formation of the S S R C -and R S S C -configured products 3a and 4b suggests that the two reactions proceed via the transition state ts2.…”
Section: About the Diastereoselectivitymentioning
confidence: 77%
“…spectrum of the resulting solution showed that the parent (1.0 g) in THF (3 ml), PhCHO (0.55 ml) and Triton B (40% in MeOH; 0.4 ml) were added and the mixture was stirred a t room temperature for 24 h. Acetic acid (55 yl) and water (0.5 ml) were added. (2)l-p-Tolysulphinyl-1-p-tolythio-2-phenylethybne (9) .-Irradiation of a solution of (2) in MeOH and chromatography on silica gel-AgNO, afforded pure (9); 6 (CDC1,)…”
Section: Methodsmentioning
confidence: 99%
“…The isolated product (4a), under the reaction conditions, gave the [Eu(tf~)~]. The resonance of the olefinic proton in (9) sarne reaction mixture: (2) (85%) and (4a) (15y0, relative ratio ca. 65 : 15 : 12 : 8).…”
mentioning
confidence: 99%
“…It is conceivable that the trio1 9 is an intermediate in this catabolism, but the origin of the N-atom in 8 is currently unknown. A related transformation is known [16] during the biosynthesis of mycophenolic acid in fungi where oxidative cleavage of the central (E)-double bond of a farnesyl moiety occurs via a diol and an c( -hydroxy ketone to give a carboxylic acid.…”
mentioning
confidence: 99%